Mental health and academic performance of students at tertiary level: the role of housing - Maqbool, Menaal; Farooq, Muhammad; Imran, Madiha; Alghafli, Maryam; Fatima, Nahid (Frontiers in Education, 2025)
This study was designed to investigate the impact of inappropriate housing on the emotional wellbeing and academic performance of university students. The cognitive development, mental health outcomes, and educational achievements of children are significantly influenced by the quality of their housing conditions. A cross-sectional study was conducted with a sample of 211 undergraduate and graduate university students. The primary aim of this study was to evaluate the impact of inadequate housing and mental health on students' academic performance, using a validated survey tool. Findings from the structural equation model show that inadequate housing is significantly associated with poorer mental health among students, highlighting housing quality as a critical social determinant of student wellbeing in Pakistan. Additionally, mental health is positively associated with academic performance, with findings suggesting that poor housing is related to lower academic performance through its association with poorer mental health.